Vaper trails: New nicotine products and the innovation principle - Victoria Hewson; Christopher Snowdon (Institute of Economic Affairs (IEA), 2022)
The benefits of innovation are unpredictable and hard to quantify. Fear of adverse consequences can lead to excessive emphasis on risk avoidance, leading to regulation that holds back beneficial innovation. The experience in tobacco harm reduction illustrates this.Innovative reduced-risk nicotine products, such as e-cigarettes, snus and heated tobacco, have been associated with steep declines in smoking prevalence in several countries, including the UK, but have been banned in others on the basis of the precautionary principle.While some residual uncertainties remain, there is ample evidence that these products will not increase the health risk to smokers who switch to them, nor to society as a whole. This evidence would not exist if every country had preemptively banned them.Those who are opposed to tobacco harm reduction tend to focus on the potential risks of alternative products, rather than their risks relative to the hazards of smoking. This is a mistake. The realistic counterfactual to a scenario in which hundreds of millions of smokers switch to lower-risk nicotine products is not one in which nicotine use disappears but one in which hundreds of millions of people continue to smoke cigarettes.Impact assessments for regulations in this field are supposed to include full cost-benefit analysis but in the case of EU laws, this has not always been reflected in the eventual legislation, and in the UK, dynamic effects on smoking cessation have been poorly addressed.Framing the use of precautionary principle in the field of tobacco harm reduction to better account for the benefits of new products in bringing about smoking cessation could improve cost-benefit analysis and regulatory outcomes. The same lesson can be carried into other policy areas.
Keywords: 330; Tobacco products; Product development; Health risk; Regulation; Great Britain; EU countries; Tabakwaren; Produktentwicklung; Gesundheitsrisiko; Regulierung; Großbritannien; EU-Staaten